Maurice Pialat. - Warehime, Marja (French film directors., 2006)
One of the most gifted directors of the post New Wave, Maurice Pialat is frequently compared to such legendary filmmakers as Jean Renoir and Robert Bresson. A quintessentially realist filmmaker, who, like Bresson, was also trained as a painter, Pialat?s particular form of realism influenced an entire generation of young filmmakers in the nineties. This volume is the first book-length study of Pialat?s cinema in English. It provides an introduction to a complex and difficult director, who saw himself as a marginal and marginalised filmmaker, but whose films are deeply rooted in French society a.